The Role of Advocates In Law Enforcement and Providing Legal Aid, Especially In The Religious Courts - Anggo Doyoharjo; Yokhebed Arumdika Probosambodo; FX. Hastowo Broto Laksito (Indonesian Journal Publisher, 2025)
This research was conducted with the aim and purpose of examining and seeing the extent of the role of advocates as law enforcers who have a role in providing services and legal assistance to judicial institutions, especially in the Religious Courts. This research uses normative legal type methods, namely research that obtains legal materials by collecting and analysing legal materials related to the problem to be discussed through a statutory approach, namely Law Number 13 of 2003 concerning Advocates. Advocates as law enforcers are recognised through Law Number 13 of 2003 concerning Advocates as a follow-up regulation to the constitution which confirms that Indonesia as a State of Law is obliged to uphold the rule of law. The results showed that the role of advocates as a law enforcement profession in the Religious Courts can provide positive value in providing legal aid considering that the Judiciary, especially the Religious Courts, has absolute competence and relative competence in cases that certainly require the role and assistance of advocates to assist litigants in fighting for their rights in court. In addition, advocates have a very important role in handling certain types of cases, including: marriage, inheritance, wills, grants, waqf, zakat, infaq, sadaqah, and sharia economics.